2016
DOI: 10.1088/1361-651x/aa52cb
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen–vacancy–dislocation interactions inα-Fe

Abstract: Abstract. Atomistic simulations of the interactions between dislocations, hydrogen atoms, and vacancies are studied to assess the viability of a recently-proposed mechanism for the formation of nanoscale voids in Fe-based steels in the presence of hydrogen. QM/MM calculations confirm EAM simulations showing that individual vacancies on the compressive side of an edge dislocation can be transported with the dislocation as it glides. EAM simulations then show, however, that vacancy clusters in the glide plane of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Hydrogen embrittles metallic materials by lowering the bond energy between metal atoms, which translates into a reduction of the fracture resistance. A number of authors have employed Density Functional Theory (DFT) to investigate the decohesion of fracture surfaces with varying hydrogen coverage (see, e.g., [27][28][29] and references therein). For example, Alvaro et al [28] computed the change in ideal fracture energy in the presence of hydrogen atoms at Σ3 and Σ5 grain boundaries in nickel.…”
Section: Hydrogen-dependent Surface Energy Degradationmentioning
confidence: 99%
“…Hydrogen embrittles metallic materials by lowering the bond energy between metal atoms, which translates into a reduction of the fracture resistance. A number of authors have employed Density Functional Theory (DFT) to investigate the decohesion of fracture surfaces with varying hydrogen coverage (see, e.g., [27][28][29] and references therein). For example, Alvaro et al [28] computed the change in ideal fracture energy in the presence of hydrogen atoms at Σ3 and Σ5 grain boundaries in nickel.…”
Section: Hydrogen-dependent Surface Energy Degradationmentioning
confidence: 99%
“…Continuum theories and simulations have shown that in the presence of hydrogen, the solute drag force exerted on a moving dislocation adds resistance to dislocation motion 14,15 and no shielding of dislocation–dislocation interactions by hydrogen can be found in atomic simulations 16 . Hydrogen segregation to grain boundaries and interactions with vacancies also play important roles in HE 1719 . A recent study suggested that vacancies can interact with hydrogen and lock dislocations motion in aluminum 20 .…”
Section: Introductionmentioning
confidence: 99%
“…Recent experiments in steels suggest that, in the presence of H, nanovoids are formed along GBs and that coalescence of these nanovoids could lead to embrittlement fracture along grain boundaries [27]. Mechanisms for this behavior remain to be uncovered, however [28,29].…”
mentioning
confidence: 99%